2001
DOI: 10.1055/s-2001-11336
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Effects of a Single Dive to 50 Meters in Sport Divers with Asymptomatic Respiratory Atopy

Abstract: Increasing popularity of sports diving makes it likely that subjects with allergic respiratory diseases will be involved in diving with self contained underwater breathing apparatus (scuba). The present study evaluated the effects of a single scuba-dive on pulmonary function in subjects with respiratory atopy. Specific airways conductance (sGaw), residual volume (RV), forced vital capacity (FVC), forced expiratory volume in 1 sec (FEV1), mid expiratory flow at 50% of FVC (MEF50), and transfer factor for carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“…After exercise, there was a significant deterioration of FEV1 and forced expiratory flow at 25-75% of FVC in the asthmatic subjects compared to both the post-exercise dry control condition and healthy control subjects [77]. In a study comparing changes in pulmonary function after a simulated wet chamber dive to 50 m between nine subjects with hay fever and nine healthy controls there were slight reductions in FVC 24 h after the dive and a reduction in specific airway conductance in the atopic subjects only [78], which was interpreted as an increased susceptibility of atopic subjects to diving exposure. Another study investigated pulmonary function in 15 atopic nonasthmatic subjects and 15 healthy controls after dry chamber dives to simulated 50 m depth and wet dives to 50 m in seawater [79].…”
Section: Effects Of Diving On Lung Function In Special Populationsmentioning
confidence: 99%
“…After exercise, there was a significant deterioration of FEV1 and forced expiratory flow at 25-75% of FVC in the asthmatic subjects compared to both the post-exercise dry control condition and healthy control subjects [77]. In a study comparing changes in pulmonary function after a simulated wet chamber dive to 50 m between nine subjects with hay fever and nine healthy controls there were slight reductions in FVC 24 h after the dive and a reduction in specific airway conductance in the atopic subjects only [78], which was interpreted as an increased susceptibility of atopic subjects to diving exposure. Another study investigated pulmonary function in 15 atopic nonasthmatic subjects and 15 healthy controls after dry chamber dives to simulated 50 m depth and wet dives to 50 m in seawater [79].…”
Section: Effects Of Diving On Lung Function In Special Populationsmentioning
confidence: 99%
“…One study revealed pronounced but minor lung function changes after a deep dive to 50 msw in a small group of asymptomatic scuba divers with airway hyperresponsiveness as assessed by methacholine challenge. [49] ASTHMA AS A CONSEQUENCE OF SCUBA DIVING?…”
Section: Airway Hyperresponsiveness and Divingmentioning
confidence: 99%
“…[47] Occasionally, airway hyperresponsiveness has been reported to be present in single experienced divers elsewhere. [48,49] Thus, among selected samples of scuba divers there are a larger number of asymptomatic divers with airway hyperresponsiveness who had dived uneventfully for years. There are as yet no data indicating an increased risk of divingrelated injury in asymptomatic subjects with airway hyperresponsiveness.…”
Section: Airway Hyperresponsiveness and Divingmentioning
confidence: 99%
“…They also demonstrated that effects on respiratory function were consistent with small airways dysfunction which may lead to long-term effects on respiratory function in SCUBA divers. 2 Cross-sectional studies have shown that divers frequently have unusually large lung volumes associated with a low forced expiratory volume in one second (FEV 1) / forced vital capacity (FVC) ratio (FEV 1%) suggestive of obstructive airways disease or airflow limitation. 3 Reduced airflow may be due to air trapping, which increases the risk of pulmonary barotrauma and arterial gas embolism during ascent.…”
Section: Introductionmentioning
confidence: 99%
“…2 The dive profile was controlled and subjects used full-face masks rather than demand valves. The study concluded that atopic divers are more susceptible to the effects of diving on lung function and suggested that divingrelated factors and diving history are associated with diminished flows in lung volumes.…”
Section: Introductionmentioning
confidence: 99%